(untitled) (Legal journal - Research in Legal and Social Sciences, 2020)
The study of organized crime reveals the lack of consensus in the systematization of expertise related to criminology which leads to insufficient contribution to its pragmatic implementation in the legal and sociopolitical framework. This paper is a limited but valid contribution to the Criminological Science. In particular, this investigation reveals the substancial referrals subscribed in the conceptual definitions, also the analysis of experiences around the globe, and the ineffective implementation of security policies that are promoted at multilateral forum. It is worth noting that, transnational crime constitute an emerging problem in constant reinvention, strenghening and growth in Latin America and Europe.